Os nomes italianos em estabelecimentos comerciais de Belo Horizonte e a relação identitária Brasil-Itália - Ivan Fagundes Batista (2009)
This study aims at mapping and analysing the Italian names in commercial shops in Belo Horizonte City no matter with complete or partial signifier in this idiom. The intention is to discover what drives the shop owners to choose names like these for their businesses, thus, contributing for the major field which investigates the relation ofidentities between Brazil and Italy. The data were collected mainly at Savassi neighbourhood, but were also spread through a random search. These collected names have undergone graphic, syntactic and semantics analyses, with the desire to spot the types of deviation they contained. Moreover, questionnaires were applied to the shopowners willing to elicit data which demonstrated their motivations. It was noted that in ¾ of the whole amount of names analysed the deviations were located and that Italianate traces in the shop owners practices were ample, however depicted characteristic of shallowness. Linked to this fact, it was also possible to perceive that the current relationship that Italy establishes both with the city and the State of Minas Gerais lights up, in the privileged economic classes, this Italianate.